Decrease of Rab11 prevents the correct dendritic arborization, synaptic plasticity and spatial memory formation - Siri, Sebastian Omar (2020)
Emerging evidence shows that Rab11 recycling endosomes (REs Rab11) are essential for several neuronal processes, including the proper functioning of growth cones, synapse architecture regulation and neuronal migration. However, several aspects of REs Rab11 remain unclear, such as its sub-cellular distribution across neuronal development, contribution to dendritic tree organization and its consequences in memory formation. In this work we show a spatio-temporal correlation between the endogenous localization of REs Rab11 and developmental stage of neurons. Furthermore, Rab11-suppressed neurons showed an increase on dendritic branching (without altering total dendritic length) and misdistribution of dendritic proteins in cultured neurons. In addition, suppression of Rab11 in adult rat brains in vivo (by expressing shRab11 through lentiviral infection), showed a decrease on both the sensitivity to induce long-term potentiation and hippocampal-dependent memory acquisition. Taken together, our results suggest that REs Rab11 expression is required for a proper dendritic architecture and branching, controlling key aspects of synaptic plasticity and spatial memory formation.